A Theory of Career Mobility - Sicherman, Nachum; Galor, Oded (Journal of Political Economy, 1990)
This paper analyzes theoretically and empirically the role and significance of occupational mobility in the labor market focusing on individuals' careers. It provides additional dimensions to the analysis of investment in human capital, wage differences across individuals, and the relationships among promotions, quits, and interfirm occupational mobility. It is shown that part of the returns to education is in the form of higher probabilities of occupational upgrading, within or across firms. Given an origin occupation, schooling increases the likelihood of occupational upgrading. Furthermore, workers who are not promoted despite a high probability of promotion are more likely to quit.